Role of Parents and Students' Learning Interest towards Student's Learning Achievement during the Covid-19 Pandemic - Eka Bekti; Rini Sugiarti (BIRCU, 2023)
Student learning achievement can be improved if students are active in learning, and learning process course there are several factors that also influence student achievement, role of parents and student interest in learning itself. This study aims to determine effect role parents and interest in learning on student achievement. Temporary hypothesis is that there is a positive and significant relationship between the role parents and interest in learning on student achievement. Using quantitative research methods with the number of respondents as many as 55 students class XI SMK Teresiana Bandungan Semarang through a scale instrument student achievement, role of parents, and interest in learning that have been tested for validity and reliability and analyzed with multiple and simple linear regression models using JASP program. Results showed that there was a positive and significant influence between role of parents and interest in learning on student achievement, either simultaneously or partially.